Treatment of municipal solid waste incineration fly ash: State-of-the-art technologies and future perspectives - Zhang, Yuying; Wang, Lei; Chen, Liang; Ma, Bin; Zhang, Yike; Ni, Wen; Tsang, Daniel C.W. (Journal of hazardous materials, 2021)
Municipal solid waste incineration (MSWI) fly ash is considered as a hazardous waste that requires specific treatment before disposal. The principal treatments encompass thermal treatment, stabilization/solidification, and resource recovery. To maximize environmental, social, and economic benefits, the development of low-carbon and sustainable treatment technologies for MSWI fly ash has attracted extensive interests in recent years. This paper critically reviewed the state-of-the-art treatment technologies and novel resource utilization approaches for the MSWI fly ash. Innovative technologies and future perspectives of MSWI fly ash management were highlighted. Moreover, the latest understanding of immobilization mechanisms and the use of advanced characterization technologies were elaborated to foster future design of treatment technologies and the actualization of sustainable management for MSWI fly ash. [Display omitted] •Review the state-of-the-art treatment technologies and recycling approaches for MSWI fly ash.•Compare the merits and demerits of various technologies for MSWI fly ash treatment.•Elaborate the latest immobilization mechanisms based on advanced characterization techniques.•Provide future perspectives for sustainable management of MSWI fly ash.